Analisis Social Return On Investment (SROI): BUMDes Mutiara Welirang Unit Wisata Taman Ghanjaran - Adisti, Yohana; Pardiman, Pardiman; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to assess the economic, social, and environmental impacts generated by investments made in BUMDes Mutiara Welirang, Taman Ghanjaran Tourism Unit, using the Social Return on Investment (SROI) analysis tool. The SROI methodology is carried out through several stages: defining the scope, mapping the impact, evidencing and valuing the impact, determining the final impact, and calculating the SROI ratio. This research employs a qualitative approach to understand the impacts of BUMDes Mutiara Welirang, Taman Ghanjaran Tourism Unit. The findings indicate that the SROI ratio is 1.59, meaning that every rupiah invested in supporting the village tourism program generates an impact value of IDR 1.59. This demonstrates that BUMDes Mutiara Welirang, Taman Ghanjaran Tourism Unit, has successfully created significant social impacts, benefiting the residents of Ketapanrame Village. Keywords : Community Empowerment, Social Impact, Investment, Social Return on Investment (SROI), BUMDes Mutiara Welirang, Village Tourism, Taman Ghanjaran.